Implementation of Character Education for Students in Inclusive Schools (Case Study of Al-Muhajirin Islamic Kindergarten, Tangerang) - Sutarman Sutarman; Agus Salim (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to analyze the implementation of character education for students in inclusive schools. A descriptive qualitative research approach was employed. The research informants consisted of the school principal, teachers, and parents. Data collection techniques included interviews, observations, and documentation. Data validity was ensured through triangulation involving data reduction, data presentation, and verification. The implementation of character education in inclusive schools was carried out in three stages: execution, habituation, reinforcement, and assessment. The implementation stage began during new student registration, focusing on instilling character values in inclusive students. The final stage involved assessing character-building outcomes. Supporting factors included teachers' motivation to enhance their competencies and parental support for the character education program. Internal obstacles involved the lack of special education graduates among some teachers, while external challenges stemmed from limited parental support. Solutions included organizing seminars and teacher training, establishing collaborations with institutions specializing in inclusive education, and fostering communication between teachers and parents through parenting programs attended by both educators and parents.